Merging Minds: A Critical Analysis of Hybridizing Islamic Education and Neuroscience - Jailani, Jailani (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
The dichotomy between neuroscience and Islamic Education has led to sluggish scientific progress and the emergence of unresolved issues. Islamic education, rooted in divine revelation, relies on reason as its foundation—a realm extensively studied in neuroscience. This research aims to investigate the potential of integrating neuroscience and Islamic Education, giving rise to the scientific field of Islamic Education Neuroscience. The study employs a qualitative literature-based approach, analyzing various theories and adopting a grounded theory methodology to shape the research objectives. The findings reveal that Islamic Education Neuroscience, encompassing the epistemology of Islam, including bayani, irfani, and burhani traditions, already exhibits scientific validity due to existing studies. However, further scientific development necessitates internalizing scientific theories, substantiating them within the epistemology of Islamic Education, and fostering integration with other Islamic education disciplines. This research holds significant implications for achieving the comprehensive goals of Islamic education, harmoniously bridging the gap between general science and Islam. The envisioned scientific development of Islamic education presents a framework for deeper understanding and practical application of knowledge, in alignment with Islamic principles, contributing to human progress.